ChemInform Abstract: Synthetic Chemistry and Biological Activity of Pentafluorosulfanyl (SF5) Organic Molecules. Issue 4 (31st January 2013) - Altomonte, Stefano; Zanda, Matteo
Abstract Review: literature published after 2000; 122 refs.